2000
DOI: 10.1002/(sici)1097-4636(200002)49:2<147::aid-jbm1>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Wear simulation of UHMWPE for total hip replacement with a multidirectional motion pin-on-disk device: Effects of counterface material, contact area, and lubricant

Abstract: The wear of nonirradiated ultra-high molecular weight polyethylene (UHMWPE) was studied with a circularly translating pin-on-disk (CTPOD) device. With this simple device, the wear of the acetabular cup is simulated. Two shapes of a polyethylene pin were used: flat wear faces of 3.0 and 8.9 mm in diameter. The load was always 70.7 N. Tests were done against stainless steel plates in serum, albumin, and gamma-globulin lubricants and against alumina plates in serum. With 3.0-mm-in-diameter wear faces, the wear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…As the degradation effects in the present tests were minimal compared with long duration tests, the measured μ values were much higher than those measured in longer tests. For example, the coefficient of friction in the present tests was 0.26-0.34 with 1.1 MPa, while it was as low as 0.05 after several days of running in the earlier wear tests [12,14]. At low p values, mixed lubrication mechanism probably prevailed, as μ increased with increasing p. On the other hand, above 1.1 MPa, the decrease of μ with increasing p suggested dry sliding.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…As the degradation effects in the present tests were minimal compared with long duration tests, the measured μ values were much higher than those measured in longer tests. For example, the coefficient of friction in the present tests was 0.26-0.34 with 1.1 MPa, while it was as low as 0.05 after several days of running in the earlier wear tests [12,14]. At low p values, mixed lubrication mechanism probably prevailed, as μ increased with increasing p. On the other hand, above 1.1 MPa, the decrease of μ with increasing p suggested dry sliding.…”
Section: Discussionmentioning
confidence: 44%
“…From the signal of the calibrated transducer-amplifier system, the coefficient of friction could be calculated. Since the slide track radius was 5 mm and the load limit of the transducer was 30 N, the maximum friction force that could be measured was shown that if several days are run with the same serum, friction may decrease for days due to serum degradation [12,14].…”
Section: Methodsmentioning
confidence: 99%
“…If miniature specimens were used, it would not be too difficult to pack even a much higher number of test stations than 100 into one CTPOD device, but it has been shown that the wear behaviour of a miniaturized contact surface is quite different from that of actual bearing surfaces in vivo [18]. Note that the Super-CTPOD specimens are not miniaturized.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive pressure is likely to lead to abnormal thermal phenomena [18]. Overheating of the tribocontact is a pitfall to be avoided in wear testing.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Antibiotics and fungicides are often used to retard bacterial and fungal growth in lubricants but there is no evidence indicating that this is effective in reducing the overall degradation of serum. On the contrary, Liao and co-workers 34,35 and Lu and McKellop 36 have shown that serum degradation is caused predominantly by frictional heating.…”
Section: Discussionmentioning
confidence: 99%